Advanced exergy and exergoeconomic analyses of a cascade absorption heat transformer for the recovery of low grade waste heat. (1st February 2020) - Wang, Yinglong; Liu, Yigang; Liu, Xiaobin; Zhang, Wanxiang; Cui, Peizhe; Yu, Mengxiao; Liu, Zhiqiang; Zhu, Zhaoyou; Yang, Sheng
Highlights: The division temperature for the proposed system based on accurate model is 136 °C. 21.28% of exergy destruction rate and 17.84% of investment cost rate are avoidable. Conventional and advanced analyses results are not always identical. The focus areas and improvement strategies are given in this paper. Abstract: For utilizing industrial low grade waste heat, a cascade absorption heat transformer is proposed in this paper. Conventional and advanced exergy and exergoeconomic analyses are used to determine the cause and avoidable degree of the exergy destruction and cost rates of the components. The analysis results show that only 21.28% of the exergy destruction rates are avoidable by improvement, while 80.2% of the investment cost rates are from the components themselves. Moreover, the advanced exergoeconomic factor shows that the optimization priority of the LiBr absorber, NH3 condenser, and NH3 absorber is different from that indicated by the conventional method. Improvement suggestions for each component are given based on the analysis. Moreover, the influence of the parameters, footprint, and control strategy on the system are also studied. These analyses have a significant effect on optimizing the components in the system.